A review on the environmental durability of intumescent coatings for steels - Anees, Sheik Mohamed (2018)
It is well known that when an unprotected steel structure is exposed to fire, depending on the section factor, the temperature of the steel increases rapidly. This increase affects the mechanical properties of the steel and could result in deformation/failure of the structure depending on the temperature, time, and applied load. Therefore, conventionally, intumescent-based coatings are used as protective coatings on steel. However, poor weathering resistance of these coatings is a major problem. Even the slightest changes in chemical composition due to weathering reduce the fire performance of these coatings. This review focuses on elaborating and exploring the protective coatings for steel, the environmental interaction of these polymer-based coatings, sorption kinetics of moisture/water, leaching of flame-retardant additives, subsequent changes in chemical composition of the coatings, and the resulting effect on fire performance of coatings. Discussions on UV degradation of polymeric materials, blister formation in weathered coatings, and corrosion susceptibility of the substrates are also incorporated in these topics.